Світоглядні орієнтири в ситуації постмодерну - Стежко, З. В.; Стежко, Г. П. (КНТУ, 2009)
Розглядаються соціокультурні трансформації на зламі епох; роль філософії та її світоглядні перспективи на тлі руйнації стереотипів Модерну. Sociocultural transformations at the edge of the periods are considered; the role of Philosophy and its world outlook prospects against the background of the Modernist style stereotypes ruining.
Keywords: раціональність; постмодернізм; гранднаративи